Shakespeare Terminology with Special Reference to Shakespeare Arden Dictionaries - Karpova, Olga (Respectus Philologicus, 2018)
The paper is devoted to the description of a special group of reference works in English author lexicography – terminological (or LSP) dictionaries of different subject areas explored in Shakespeare’s works: ethics, religion, military and naval activities, medicine, music, politics and society, philosophy, theatre, etc. As stated by scholars, Shakespeare is considered to be an expert in nineteen subject fields whose terms are used in their direct and figurative meaning in the Bard’s creative works. Among more than one hundred types of Shakespeare’s linguistic and encyclopaedic reference works, his terminological dictionaries play a significant role, registering and describing special groups of terms from the author’s plays. Shakespeare LSP reference books are combined today into Arden Shakespeare Dictionaries. The article discovers specific features of the architecture of Shakespeare LSP dictionaries: mega-, macro- and microstructure, using the recently published dictionary “Shakespeare’s Plants and Gardens” (2016). Detailed analysis of the unique Shakespearean use of plant and garden names contribute to better understanding of their symbolism and aesthetic value in Shakespeare’s plays.